Enfants travailleurs au Portugal et au Pérou - Antonella Invernizzi (Cahiers de la Recherche sur l'Education et les Savoirs)
This article describes the findings of two qualitative researches carried out with working children and their families in Lima (Peru) and the Algarve (Portugal). They focus on the socialisation of the working child, related to the experience and skills gained through work, as well as the socio-economic strategies which provide the context of that learning process.Analysis shows that work might be a space in which the child gains important skills and knowledge. Their relevance cannot, however, be assessed without proper examination of economic conditions and of the labour market, of the accessibility and efficiency of the school system and of professional training as well as an analysis of the work opportunities that qualifications might or might not provide.